Optimasi BIPV berdasarkan produksi energi listrik dan masa pengembalian investasi - Susan; Dyah Kusuma Wardhani; Yusuf Ariyanto; Eric Harianto (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The availability of non-renewable resources to generate electrical energy has decreased. The National Energy Council says that Indonesia has huge potential renewable energy resources. The largest amount coming from solar energy. However, only 5% is utilized. The number of building owners who want to install the technology related to renewable energy on/in a building in Indonesia is still very small. This happens due to the high initial cost of installation. In case of an existing building, the boundaries added with the limitation of structure and limitation of potential-available integrated area. This study proposed a BIPV model in an existing building to contribute the maximum use of renewable energy in a relatively limited potential-available integrated area. The experimental method was applied to several models. Amount of electrical energy generated, and ROI were used as optimization parameters. ROI will give more comprehensive review to a building owner, to show that the time period is the most critical determinant of investment. The study shows that installation of PV on an opaque wall in the west orientation is the optimum one. The model generated 777741 kWh/year of electrical energy, exceeding the existing consumption. ROI calculated in 4.36 years, relatively short compared to 25 years of PV life guarantee. The optimization on this model is supported by its largest number of integrated area and high annual radiation received. This study shows significant results to the building owner. Electrical energy and ROI should be fully taken as a consideration of when to decide to apply PV.